1985
DOI: 10.1172/jci111732
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein suppresses feedback control of glomerular filtration in rats.

Abstract: We have examined the possibility that changes in glomerular filtration rate (GFR) after changes in dietary protein intake may depend on altered function of the tubuloglomerular (TG) feedback system. We studied male Sprague-Dawley rats after dietary pretreatment for 9.6±3.6 (SD) d with isocaloric diets containing either 6% or 40% casein. We found that GFR in rats fed the high protein diet was 24-29% higher than in rats fed the low protein diet. Simultaneous measurements of single nephron GFR (SNGFR) in the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The mechanisms that mediate the acute renal response to a protein or amino acid load are not well defined, although some authors have considered that this response in induced by glucagon (Parving et al 1985), a liver-derived renal vasodilator (Premen 1985;Dratwa et al 1984) glomerulopressin (Alvestrand and Bergstrom 1984), tobule-glomerular feedback (Seney and Wright 1985), prostaglandins (Krishna et al 1988). In the present study, the mechanism of this response was not elucidated, but the finding that loading a vegetable protein did not increase GFR might provide some clarification.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms that mediate the acute renal response to a protein or amino acid load are not well defined, although some authors have considered that this response in induced by glucagon (Parving et al 1985), a liver-derived renal vasodilator (Premen 1985;Dratwa et al 1984) glomerulopressin (Alvestrand and Bergstrom 1984), tobule-glomerular feedback (Seney and Wright 1985), prostaglandins (Krishna et al 1988). In the present study, the mechanism of this response was not elucidated, but the finding that loading a vegetable protein did not increase GFR might provide some clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the hyperfiltration observed with protein feeding (90) and uninephrectomy (19,24) and in pregnancy (11). Evidence implicates a chronic resetting of TGF in such settings and in the hyperfiltration seen in diabetes (141,158). Longer-acting adaptations to elevated pressure may also exist, and such mechanisms could contribute to the observed lack of impact of acute autoregulatory impairment on volume homeostasis.…”
Section: Regulation Of Rbf and Gfr Independent Of Autoregulatory Respmentioning
confidence: 99%
“…Microperfusion studies by Seney et al (68) determined that protein-induced increases in GFR result from changes in the tubuloglomerular feedback (TGF) system. Their studies found that the sensing mechanism of the TGF system was rendered less responsive by high protein intake and that the diminished TGF was caused, at least in part, by a reduced early distal NaCl concentration, without a change in early distal tubule osmolality (69). However, the cause of the reduced luminal NaCl concentration remains unknown.…”
Section: Urea Recycling and Regulation Of Gfr By High-protein Dietsmentioning
confidence: 99%